2010
DOI: 10.1007/s00339-010-6157-3
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni effect induced micro/nano-patterning on Sb2Te3 phase change thin film by laser pulse

Abstract: Thermocapillary and chemicapillary effects are known to coexist in a material molten pool when irradiated by a pulse laser. According to the effects, we fabricate various patterns with different shapes on a Sb 2 Te 3 phase change thin film by precisely adjusting the pulse energy. In this process, the laser power is fixed at 5.0 mW, and the pulse width is adjusted from 100 ns to 5 ns. The shape of the patterns gradually changes from a dimple-bowl shape, a dome shape, a "Sombrero" shape to a deep-bowl shape foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Both the effects oen coexist during the process and compete with each other to form different shape patterns as reported in the literature. 41 A "sombrero" shape of the patterned structure in Fig. 4(c) and 7 is observed.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Both the effects oen coexist during the process and compete with each other to form different shape patterns as reported in the literature. 41 A "sombrero" shape of the patterned structure in Fig. 4(c) and 7 is observed.…”
Section: Resultsmentioning
confidence: 83%
“…According to the Marangoni effect, the surface tension of the molten ow depends not only on the surface temperature gradient, but also on the surfactant concentration gradient, which corresponds to the chemicapillary effect due to the different chemical potentials in the conned molten pool. [40][41][42] The thermocapillary effect pushes the molten materials toward the cold region that has higher surface tension, whereas the chemicapillary pushes the liquid material toward the hot region that has higher surface energy and low surfactant concentration. Both the effects oen coexist during the process and compete with each other to form different shape patterns as reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Dun et al studied the laser-pulse-induced deformation of 50-nm-thick Sb 2 Te 3 films due to a competition between thermocapillary and solutocapillary effects. 70 A displacement of material out of the laser spot was observed for low powers, whereas material accumulation in the laser spot occurred for higher powers. Verma et al irradiated polystyrene and poly(methyl methacrylate) layers with intense near-UV radiation at 355 nm, which caused local melting of the polymer.…”
Section: Introductionmentioning
confidence: 94%
“…They performed a linear stability analysis as well as numerical simulations of the evolution equations for the height and reactant concentration profiles. Dun et al studied the laser-pulse-induced deformation of 50-nm-thick Sb 2 Te 3 films due to a competition between thermocapillary and solutocapillary effects . A displacement of material out of the laser spot was observed for low powers, whereas material accumulation in the laser spot occurred for higher powers.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with fast-evolving nanotechnology, intensive efforts [3][4][5] are being focused on pattern structure in SbTe-based films because of their promising applications in optic-electronic devices. These applications are based on interaction of laser beams with films, numerous research 6,7 have shown that generally these materials exhibit optical nonlinearities even at low irradiance intensity, and the optical nonlinearities should play an important role when these materials are used as optical recording medium and mask layer materials.…”
Section: Introductionmentioning
confidence: 99%